Perbedaan Motivasi Belajar dan Percaya Diri Antara Siswa Yang Berasal Dari Keluarga Utuh Dengan Keluarga Broken Home - Rakhmawatiningtyas, Sustin (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. The main purposes of this research are to find the differences of learning motivationÂ Â  and self-confidence of students come from intact family or peace family and the broken family. The subjects in this study were 100 students come from SMA Negeri I Panji Situbondo. They were 50 students from intact families and 50 students from families broken home. Data analysis was used statistical t-test. Results showed learning motivation of students come from intact families is more high than student from broken families. Adversly, students come from intact families are less confident than students from broken families. Further, the results will be discussed in this article.Keywords: intact family and broken, learning motivation, self-confidence